2019
DOI: 10.5194/bg-16-3583-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of ocean biogeochemistry to the iron supply from the Antarctic Ice Sheet explored with a biogeochemical model

Abstract: Abstract. Iron (Fe) delivery by the Antarctic Ice Sheet (AIS) through ice shelf and iceberg melting enhances primary productivity in the largely iron-limited Southern Ocean (SO). To explore this fertilization capacity, we implement a simple representation of the AIS iron source in the global ocean biogeochemical model NEMO-PISCES. We evaluate the response of Fe, surface chlorophyll, primary production, and carbon (C) export to the magnitude and hypothesized vertical distributions of the AIS Fe fluxes. Surface … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 105 publications
(226 reference statements)
3
38
1
Order By: Relevance
“…Wadley et al (2014) estimated the contribution of Fe in sea ice to SO primary production to 11%, which is significantly lower than their 75% estimated for the sedimentary Fe source. For C export, a contribution of sea ice of less than 4% is estimated in the SO (Wang et al, 2014), which falls within the 1-30% range of the contribution estimated for the iceberg-ice shelf Fe source (Laufkötter et al, 2018;Person et al, 2019;Wadley et al, 2014).…”
Section: Should Primary Production and Carbon Export Estimates Be Revsupporting
confidence: 75%
See 3 more Smart Citations
“…Wadley et al (2014) estimated the contribution of Fe in sea ice to SO primary production to 11%, which is significantly lower than their 75% estimated for the sedimentary Fe source. For C export, a contribution of sea ice of less than 4% is estimated in the SO (Wang et al, 2014), which falls within the 1-30% range of the contribution estimated for the iceberg-ice shelf Fe source (Laufkötter et al, 2018;Person et al, 2019;Wadley et al, 2014).…”
Section: Should Primary Production and Carbon Export Estimates Be Revsupporting
confidence: 75%
“…Although nonlinear, but showing a clear trend in which higher primary productivity is associated with higher C export in the model (Person et al., 2019), the contribution of sea ice to primary productivity results in an increase in C export ranging from 9% to 19% in all four experiments relative to CTL. The increase in C export is at least twice as high as that of Wang et al.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Duprat et al 7 , recently suggested, using satellite-derived chlorophyll data, that icebergs drive >20% of Southern Ocean particulate organic carbon export (POC). This is supported by one model estimate of 30% for Antarctic runoff and icebergs 17 , yet other estimates of iceberg fertilization vary widely and are in some cases significantly smaller 8,9,18,19 . Similarly, there is disagreement about whether iceberg fertilization is more, or less, efficient as iceberg size increases 7,8 .…”
Section: Introductionmentioning
confidence: 75%